DEVELOPMENT OF A MULTIMODAL RECOGNITION SYSTEM AND TARGET CLASSIFICATION BASED ON ARTIFICIAL INTELLIGENCE - Ніколюк, Петро; Сапожнікова, Вероніка; Чемес, Владислав (SWorldJournal, 2025)
The study addresses the problem of developing a multimodal system for target recognition and classification based on artificial intelligence. The relevance of the topic stems from the need to improve the reliability of automatic object detection under co